The Role of Internal Control in Cash Management in Small and Medium Enterprises - Doni Wirshandono Yogivaria; Supami Wahyu Setiyowati (Universitas Islam Bandung, 2023)
AbstractThe purpose of this study is to show the importance of effective internal control in newly established Small and Medium Enterprises and to give importance to internal control for business actors as a means of preventing irregularities. This research is a qualitative research with a phenomenological approach. The object of this research is Shita Farma. The selected informants were 5 employees of Shita Farma. Data collection techniques used are data reduction, data exposure, and data display. The results of the study indicate the ineffectiveness of internal control which causes deviations that impact on the inefficient business as one of the factors of employee fraud.Keywords: Control, internal, qualitative, effective, efficient AbstractTujuan penelitian ini ialah untuk menunjukkan pentingnya pengendalian internal yang efektif pada Usaha Kecil dan Menengah yang baru didirikan dan untuk memberikan pentingnya pengendalian internal bagi pelaku usaha sebagai alat pencegahan dalam penyimpangan. Penelitian ini merupakan suatu jenis penelitian kualitatif melalui pendekatan fenomenologi. Objek penelitian ini ialah Shita Farma. Informan yang dipilih adalah 5 karyawan Shita Farma. Pada metode pengumpulan data, data dilakukan melalui beberapa tahap, tahap tersebut ialah reduksi data, pemaparan data, dan tampilan data. Hasil penelitian menjelaskan bahwa kurang efektifnya pengendalian internal yang menyebabkan terjadinya penyimpangan yang berimbas pada tidak efisiensinya usaha sebagai salah satu faktor kecurangan yang dilakukan pegawai.Keywords: Kontrol, internal, kualitatif, efektif, efisien